Over-the-counter medicine abuse – A pharmacist’s emerging responsibility - Baby John, Martin; Rose MS, Alasandra; Jacson, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
Self-medication is an essential component of the healthcare system. Over-the-counter medications (OTC) are components of self-medication. The administration of OTC medications in patients increases the risk of abuse of these drugs. With pharmacists being as accessible as they are, pharmacists are the first line of contact in purchasing OTC medications and have an upper hand in ensuring safety, and efficacy and preventing abuse in patients. This review aims to give brief information on OTC medications along with their abuse. The importance of patient and pharmacist interaction has been discussed. In addition, the potential for a behind-the-counter drug category and its prospective role in improving pharmacist-patient relations have been elaborated. This review gives knowledge on the barriers faced by pharmacists in OTC medication abuse and how it can be controlled and managed effectively. The current health system should work more effectively to provide a striking balance between the purchase of OTC medications and their abuse.